A Novel and Efficient Dyes Degradation Using Bentonite Supported Zero‐Valent Iron‐Based Nanocomposites. Issue 1 (7th January 2020) - Sabouri, Mohammad Reza; Sohrabi, Mahmood Reza; Moghaddam, Ali Zeraatkar
Abstract: In this research, different nanocomposites were synthesized based on bentonite supported with zero‐valent iron in mono‐, bi‐, and tri‐metallic systems and used to degrade two model anionic dyes, methyl orange and Congo red, from wastewaters. The synergic effect between bentonite and the nanoscale zero‐valent iron‐based tri‐metallic system was investigated along with degradation efficiencies. It was found out that bentonite supported with Fe−Cu‐Ag tri‐metallic nanoscale system yields higher degradation efficiency and maximum synergic effect for both of dyes occurs, especially at acidic medium. Therefore, the characterization of this nanocomposites was conducted by BET, FTIR, SEM‐EDX, TEM and XRD which demonstrated successful loading of nanoscale Fe−Cu‐Ag tri‐metallic onto bentonite clay. All involved variables affecting the dye degradation efficiencies were modeled and optimized using central composite design under batch adsorption procedure. The Nelder‐Mead non‐linear optimization algorithm was used and the outcomes showed the optimum conditions regarding the removal of 300 ppm of both dyes, for the nanocomposites dose of 4.0 mg.mL −1, pH of 3 and contact time of 18 min were attained. Furthermore, dyes adsorption kinetics were investigated. In addition, the proposed nanocomposite was successfully applied to reduce the concentration of methyl orange and Congo red as hazardous dyes in the water and wastewater samples. Abstract : In this work, different nanocomposites were synthesized based on bentonite supported with zero‐valent iron in mono‐, bi‐, and tri‐metallic systems and used to degrade two model anionic dyes, methyl orange and Congo red, from wastewaters.